Brain acetylcholinesterase activity in mild cognitive impairment and early Alzheimer's disease. Issue 1 (1st January 2003) - Rinne, J O; Kaasinen, V; Järvenpää, T; Någren, K; Roivainen, A; Yu, M; Oikonen, V; Kurki, T
Abstract : Objective: Brain acetylcholinesterase activity was determined in healthy controls and in patients with mild cognitive impairment and early Alzheimer's disease. Methods: A specific acetylcholinesterase tracer, [methyl- 11 C] N -methyl-piperidyl-4-acetate ([ 11 C]MP4A), and a three dimensional PET system with magnetic resonance coregistration were used for imaging. Results: There was a significant difference in the acetylcholinesterase activity in the hippocampus between the groups (p = 0.03), the mean (SD) acetylcholinesterase activity (k3 values, min −1 ) being 0.114 (0.036) in controls, 0.098 (0.023) in mild cognitive impairment, and 0.085 (0.022) in Alzheimer's disease. The mini-mental state examination score showed no significant relation with acetylcholinesterase activity in any brain area in the combined mild cognitive impairment/Alzheimer group. Conclusions: Hippocampal acetylcholinesterase activity is only slightly reduced in mild cognitive impairment and early Alzheimer's disease and so the value of in vivo acetylcholinesterase measurements in detecting the early Alzheimer process is limited.